The feedback related negativity encodes both social rejection and explicit social expectancy violation - Sun, Sai; Yu, Rongjun (Frontiers in Human Neuroscience, 2014)
Humans consistently make predictions about the valence of future events and use feedbacks to update initial predictions. While the valence of outcomes provides utilitarian information, the accuracy of predictions is crucial for future performance adjustment. The feedback related negativity (FRN), identified as a marker of reward prediction error, possibly encodes social rejection and social prediction error. To test this possibility, we used event related potential techniques combined with social tasks in which participants make explicit prediction (whether others will accept their ‘friend request’ or not, Experiment 1) or implicit prediction (whether they would like this person or not, Experiment 2) respectively and then receive social feedback. We found that the FRN is sensitive to social rejection and explicit social prediction error in Experiment 1 but not implicit social prediction error in Experiment 2. We conclude that the FRN encodes social rejection and explicit social expectancy violation.